GLOBAL COMPACT ON MIGRATION: LEGAL NATURE AND POTENTIAL IMPACT ON THE DEVELOPMENT OF INTERNATIONAL MIGRATION LAW - Krasić, Bogdan; Stojanović, Bojan (Pravni zapisi, 2020)
International migration, both forced and voluntary, represents a prominent phenomenon in modern society, which is gaining public attention in countries of origin, transit and destination. However, the issue of migration has not been significantly regulated internationally to date, and the pioneering endeavour has taken place with the adoption of the Global Compact for Safe, Orderly and Regular Migration. A major issue that will continue to gain public attention is the future impact of the Global Compact on the formation of the body of international migration law. Although formally not a legally binding document, adoption of the Global Compact was followed by criticism precisely in regard to its potential legally binding force, actual or presumed. For proponents, it represents a starting point for creating adequate migration policies that are consistent with international human rights law, sustainable development, labour market needs and other policies. This study analyses the legal nature of the Global Compact from the soft law perspective as a source of international law and the initial steps in its implementation to determine states’ adherence to its provisions and the potential impact on the development of international migration law.
Keywords: Global Compact for Migration; New York Declaration; migration; international migration law; migration governance; soft law; sources of international law; human rights